Preparation of a hydroxyapatite–silver gradient bioactive ceramic coating with porous structure by laser cladding: A study of in vitro bioactivity. Issue 20 (15th October 2022) - Deng, Zixin; Liu, Defu; Xiong, Yi; Zhu, Xiangcheng; Li, Shengchen; Liu, Jian; Chen, Tao
Abstract: Porous coatings play a critical role in osseointegration between the artificial joint implant and host bone. Herein, a previously developed hydroxyapatite–silver (HA-Ag) gradient bioactive ceramic coating with a three-layer structure is further improved. Through laser cladding, a bioactive porous ceramic coating was prepared by adding carboxyl multi-walled carbon nanotubes (CMWCNTs) to HA powder. In this study, the effects of the added amount of CMWCNTs on the pore size, porosity, and active substance content were investigated. The results showed that the porous structure of the bioactive surface layer was gradually changed from the round hole shape to the reticular porous shape when the addition amount of CMWCNTs was increased from 5 wt % to 20 wt %, and the most appropriate amount of CMWCNTs was 10 wt %. In addition, the biocompatibility of the porous ceramic coating, as well as its effect on the alkaline phosphatase (ALP) activity of osteoblasts, were evaluated in vitro. Simulated body fluid (SBF) soaking tests were applied to determine the changes in ion concentration and calculate the concentration quotient and transfer free energy of Ca 2+ and PO 4 3 − during the soaking period in SBF. The effects of the porous ceramic coating on the nucleation and growth of HA were also validated. The results showed that the preparation of the gradient porous ceramic coating was beneficial to the nucleation and growth of apatite, further improving the bioactivity of the coating to achieve osseointegration between the artificial joint implant and host bone.